A job you mostly won't know how to do : a novel - Fromm, Pete, 1958- (Counterpoint, 2019)
"A taciturn carpenter has been too busy putting the final details on others' homes to pay much attention to his own fixer-upper. But when his wife becomes pregnant with their first child, he realizes he'll need to apply his art closer to home. For Taz and Marnie, their dreams are coming into focus, sustained by their deep sense of love and now family. The blueprint for the perfect life eludes Taz, plummeting him head first in the new strange world of fatherhood, of responsibility and late nights and unexpected joy and sorrow. It is a deceptively small novel with a very big heart" --